Measuring entertainment and automatic generation of entertaining games. (17th September 2010) - Halim, Zahid; Baig, A. Rauf; Mujtaba, Hasan
Over the period of time computer games have became a major source of entertainment for humans. From the point of view of game developers there is a constant demand of writing games which are entertaining for the end users but entertainment itself is of subjective nature. It has always been difficult to quantify the entertainment value of the human player. The two factors which mainly influence the entertainment value are the type of the game and the contents of the game. In this paper we address the issues of measuring entertainment and automatic generation of computer games. We present some quantitative measures for entertainment in a genre of computer game and apply them as a guide for the evolution of new interesting games.